WORK-NONWORK BOUNDARY MANAGEMENT AND WELLBEING AMONG ONLINE WOMEN ENTREPRENUER: ROLE IDENTITY AS A MODERATOR - MAZLYEN, SAMAH (Universiti Malaysia Sarawak (UNIMAS), 2021)
The purpose of this research is to determine the role of identity as a moderator on the relationship between work-non-work boundary management and wellbeing among online women entrepreneurs. The research questionnaire was distributed to founders and owners of small and medium companies in various industries in Malaysia, particularly entrepreneurs operating online businesses for at least six months. Sampling is carried out by snowball sampling technique starting from Byond Success Sdn. Bhd, a training agency through their professional and personal network. Pearson correlation and Spearman correlation were used to testing the hypotheses, and the results indicate that work and non-work boundary management activities have not influenced online women entrepreneurs’ wellbeing. Additionally, the moderating effect was examined using hierarchical regression analysis. The results indicate that role identity does not moderate the effect association between worknonwork boundary management characteristics and wellbeing among online women entrepreneurs. The results of this study may provide other possible explanations, useful information, and knowledge for both future practitioners and researchers to improve the current policies on work-life balance.